Smoothed finite element method for two-dimensional elasto-plasticity - Bordascorres, Stéphane Pierre Alain; Nguyen-Dang, Hung; Phan-Phuong, Quyen; Nguyen-Xuan, Hung; Natarajan, Sundararajan; Duflot, Marc (Vietnam Journal of Mechanics, 2009)
This communication shows how the smoothed finite element method (SFEM) very recently proposed by G. R. Liu [14] can be extended to elasto-plasticity. The SFEM results are in excellent agreement with the finite element (FEM) and analytical results. For the examples treated, the method is quite insensitive to mesh distortion and volumetric locking. Moreover, the SFEM yields more compliant load-displacement curves compared to the standard, displacement based FE method, as expected from the theoretical developments recently published in [4], [3] and [6].